E-SAAS: Web based development of grade report students assessment analysis system / Muhammad Farhan Misnan - Misnan, Muhammad Farhan (Faculty of Computer and Mathematical Sciences, 2007)
The main purpose of this research is to assist top management in FTMSK, UiTM to monitor students' results and performances. This research focused on the development of students' grade and assessment analysis system prototype which can give long term benefits to them. This research also concentrates on design, best approach and characteristic for designing DSS and finding the type of analysis used among program coordinator in FTMSK. This application is developed using the open source software such as Apache Web Server, MySQL Database, phpMyAdmin Database Administrator plus with PHP programming language. System Development Life Cycle (SDLC) is selected as the project development methodology. The designing phase is based on research made in literature review and the system prototype is implemented according to the type analysis retrieve from interview. Therefore, this application is really hope can assist top management in monitoring students performances and also can help better than exiting system.